1991
DOI: 10.1136/hrt.65.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Lipomatous hypertrophy of the interatrial septum: an unusual intraoperative finding.

Abstract: Lipomatous hypertrophy of the interatrial septum was an incidental finding in a man of 45 undergoing coronary artery bypass grafting for unstable angina. He was not overweight and did not have any rhythm disturbances. The diagnosis was made on frozen section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The diagnosis during a person's lifetime is rarely made, because LHIS has no typical symptoms and can be misdiagnosed. However, in autopsy the reported incidence is about 1% [4,7] but in transthoracic echocardiography reports, the incidence reaches 8% [8] and in new studies, the results showed an International Journal of Cardiology 121 (2007) 4 -8 www.elsevier.com/locate/ijcard incidence of 2.2% [9,10] revealing that the incidence is much higher than that of the autopsy. This can be explained by the increasing age of the general population and also by the great improvement of the technology in imaging techniques (CT scanning).…”
Section: Incidencementioning
confidence: 90%
“…The diagnosis during a person's lifetime is rarely made, because LHIS has no typical symptoms and can be misdiagnosed. However, in autopsy the reported incidence is about 1% [4,7] but in transthoracic echocardiography reports, the incidence reaches 8% [8] and in new studies, the results showed an International Journal of Cardiology 121 (2007) 4 -8 www.elsevier.com/locate/ijcard incidence of 2.2% [9,10] revealing that the incidence is much higher than that of the autopsy. This can be explained by the increasing age of the general population and also by the great improvement of the technology in imaging techniques (CT scanning).…”
Section: Incidencementioning
confidence: 90%
“…Mass-forming reactive and pseudoneoplastic growths are less common, but recognising and distinguishing these lesions from the neoplasms they resemble is critical to appropriate patient care. Tumours of the heart, whether neoplastic or not, are infrequently encountered in surgical or autopsy pathology 4. Their scarcity and the spectrum of lesions spanning reactive conditions, and both benign and malignant neoplasms, often generate considerable diagnostic difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Mesodermal tissues are drawn into the wall of the primitive atrial septum during this process and pockets of entrapped adipose tissue remain after the heart is fully formed. In some patients, through as-of-yet undetermined processes (presumably the same ones governing this phenomenon in epicardial fat), the entrapped adipose tissue expands, resulting in bulging of the atrial septum, that can become more than 15 or 20 mm thick 4. This is most prominent in the right atrium (since the limbus is a right atrial structure).…”
Section: Discussionmentioning
confidence: 99%
“…Kod više od polovine bolesnika sa miksomom inicijalni auskultatorni nalaz je normalan 21 . Kada se počne auskultatorno "prikazivati", čuje se ejekcioni sistolni šum, holosistolni šum kao odraz mitralne insuficijencije, dijastolni šum kod ispoljene mitralne stenoze, glasan S1, S2 i S4, klik otvaranja i drugi fenomeni koji su raznoliki.…”
Section: Diskusijaunclassified